2004
DOI: 10.1021/ja030544b
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Atomic Gold Anions toward Oxygen and the Oxidation of CO:  Experiment and Theory

Abstract: Results for the binding of carbon monoxide and oxygen along with the oxidation of CO in the presence of atomic Au(-) have been obtained utilizing a fast-flow reactor mass spectrometer. In addition, density functional calculations have been performed to explain the experimental findings. It was observed that upon oxygen addition to the metal plasma, gold oxide species of the form AuO(n)(-), where n = 1-3, were produced. The addition of carbon monoxide to the preoxidized gold atom revealed that AuO(-) and AuO(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
176
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(190 citation statements)
references
References 28 publications
9
176
0
4
Order By: Relevance
“…Prior to the experimental investigations of Haruta [58], gold was considered to be inert. In recent years, numerous experimental and theoretical studies have revealed the contrary, prompting extensive work to elucidate the mechanisms involved [59][60][61][62][63][64][65][66][67]. Important remaining questions included: Do small gold clusters contribute to the presence of O-atoms sufficient to promote oxidation of CO; and what is the influence of charge accumulation or deficiency on the reactivity?…”
Section: Elucidating Mechanisms Of Catalytic Reactionsmentioning
confidence: 99%
“…Prior to the experimental investigations of Haruta [58], gold was considered to be inert. In recent years, numerous experimental and theoretical studies have revealed the contrary, prompting extensive work to elucidate the mechanisms involved [59][60][61][62][63][64][65][66][67]. Important remaining questions included: Do small gold clusters contribute to the presence of O-atoms sufficient to promote oxidation of CO; and what is the influence of charge accumulation or deficiency on the reactivity?…”
Section: Elucidating Mechanisms Of Catalytic Reactionsmentioning
confidence: 99%
“…2 Typical catalysts for CO oxidation consist of noble metals, such as Pt, [3][4][5][6][7][8] Pd, 5,6,[9][10][11][12] Ru 13 and Au, [14][15][16][17] and they have been widely investigated for decades. To further increase the catalytic performance and reduce the cost, recent research attention has turned to ''single atom catalysts'' (SACs) 18,19 by downsizing the catalyst to the atomic scale, which provides a platform for the establishment of new fundamental science as well as the design of excellent catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…41 CO oxidation on anionic gold clusters occurs via the EleyRideal mechanism, 38, 51, 52 while CO oxidation on cationic gold atoms can occur via both Eley-Rideal and LangmuirHinshelwood mechanisms. 52 Therefore, the charge state of gold particles (which can be controlled by the support) can considerably influence their reactivity and define the reaction mechanism. 47,48,53 On the other hand it is commonly accepted that the inert supports, such as SiO 2 or hexagonal boron nitride (h-BN), do not affect the electronic and geometric structure of the supported clusters.…”
Section: Introductionmentioning
confidence: 99%